The Role of Social Media in Developing Intercultural Competence - Nurfadil Arham; Magdahalena Tjalla; Arqam (Universitas Muhammadiyah Palu, 2024)
This phenomenology study employs interviews into 10 undergraduated students of English education program at IAIN Parepare as participants. This research aims 1) to explore the experiences of the students regarding the usage of social media to interact with people from different cultural backgrounds, and 2) to investigate how the use of social media contributes into development of students' intercultural competence. The findings display that utilizing social media plays an important role in exposing students to the numerous cultural practices and traditions, thereby improving their knowledge and recognition of various cultures. Students described learning about various cultural celebrations and customs through communication in social media. Furthermore, social media facilitates them adapt their communication effectively when interacting with people from different cultures, maintaining improved sensitivity and awareness into cultural variations. The students emphasized the significance of understanding cultural distinction and avoiding misunderstandings in cross-cultural communication. However, this research still perceives few limitations including a small sample size and potential for self-reporting bias, indicating the necessity in validating and advancing upon these insights for further studies.